PhysiPKPD: A pharmacokinetics and pharmacodynamics module for PhysiCell - Daniel Bergman; Lauren Marazzi; Mukti Chowkwale; Deepa Maheshvare M; Supriya Bidanta; Tarunendu Mapder; Jialun Li (GigaByte, 2022)
Pharmacokinetics and pharmacodynamics (PKPD) are key considerations in any study of molecular therapies. It is thus imperative to factor their effects into any in silico model of biological tissue involving such therapies. Furthermore, creating a standardized and flexible framework will benefit the community by increasing access to such modules and enhancing their communicability. PhysiCell is an open-source physics-based cell simulator, i.e., a platform for modeling biological tissue, that is quickly being adopted and utilized by the mathematical biology community. We present here PhysiPKPD, an open-source PhysiCell-based package that allows users to include PKPD in PhysiCell models.